Mutation of N-glycosylation Sites in Salmonid Alphavirus (SAV) Envelope Proteins Attenuate the Virus in Cell Culture - Ida Aksnes; Turhan Markussen; Stine Braaen; Espen Rimstad (Viruses, 2020)
Salmonid alphavirus (SAV) is the cause of pancreas disease and sleeping disease in farmed salmonid fish in Europe. The spread of these diseases has been difficult to control with biosecurity and current vaccination strategies, and increased understanding of the viral pathogenesis could be beneficial for the development of novel vaccine strategies. N-glycosylation of viral envelope proteins may be crucial for viral virulence and a possible target for its purposed attenuation. In this study, we mutated the N-glycosylation consensus motifs of the E1 and E2 glycoproteins of a SAV3 infectious clone using site-directed mutagenesis. Mutation of the glycosylation motif in E1 gave a complete inactivation of the virus as no viral replication could be detected in cell culture and infectious particles could not be rescued. In contrast, infectious virus particles could be recovered from the SAV3 E2 mutants (E2319Q, E2319A), but not if they were accompanied by lack of N-glycosylation in E1. Compared to the non-mutated infectious clone, the SAV3-E2319Q and SAV3-E2319A recombinant viruses produced less cytopathic effects in cell culture and lower amounts of infectious viral particles. In conclusion, the substitution in the N-linked glycosylation site in E2 attenuated SAV3 in cell culture. The findings could be useful for immunization strategies using live attenuated vaccines and testing in fish will be desirable to study the clone’s properties in vivo.